Koloryt pogranicza serbsko-tureckiego w polskich przekładach prozy Borisava Stankovicia - Filipek, Małgorzata (Przekłady Literatur Słowiańskich, 2011)
The atmosphere of a Serbian-Turkish borderland in the Polish translations of Borisav Stanković’s prose Works of Borisav Stanković, who introduced the atmosphere of his home town Vranje, are the space of the two cultures dialogue: — his own (Serbian) and the strange (Turkish). The last one formed the mentality and the life style of the inhabitants of this region during more that five centuries of Turkish bondage. Thanks to the translations the picture of the Serbian-Turkish borderland has been recorded in Polish readers consciousness. The descriptions of family celebrations, ceremonies and rites interweave there with the scenes of everyday life. However, despite the strong Stanković’s bonds with the concrete geographical region, the reader can find in translations the universal message about human condition and about the man who — in the situation of confrontation with restrictions and prohibitions imposed by the society — loses his battles and cannot fulfil his emotional and physical needs.